Proteins from Benincasa hispida Fruit Juice: Chemical Characterization Using Total Hydrolysis, Gel Permeation Chromatography and SDS PAG Electrophoresis - Mazumder, Sutapa; Laskar, Subrata; Ghosal, Prodyot; Ray, Bimalendu (Asian Journal of Chemistry, 2016)
The juice was extracted from the matured fruit of Benincasa hispida and proteins isolated there from by precipitation with ethanol. Glutamic acid, aspartic acid, phenylalanine, leucine, threonine, serine, glycine, alanine and valine were the major amino acids present in these proteins. Gel permeation chromatography on Sephadex G-200 of the isolated protein indicates the presence of at least two populations. SDS-PAG electrophoresis study showed the presence of two populations having molecular weights 11,500 Da and 58,900 Da.